Grow Enterprise / Aslina Sidin... [et al.] - Sidin, Aslina; Marikus, Meredolyin; Jahani, Norsalina; Robert, Rachel Serna; Mat Noor, Zainora (2010)
This Business Plan is being prepared as a means of a guideline for the running of our business in the near future. Our business, namely Grow Enterprise, is going to venture into mushroom farming business which is under agricultural sector. The types of mushroom that we are going to plant are; Shiitake mushroom, Monkey Head Mushroom and Grey Oyster Mushroom. This business will be established by means of partnership and we consist of five partners. Each of us will be responsible for different field. For capital contribution, under partnership agreement, each of us will contribute our own capital to the business and the business ratio for profit and losses is equally divided. The vision of our business is to be the largest mushroom supplier in Sabah whilst among our mission are; to be competitive in producing a high quality mushroom as well as to meet the increasing demand of mushroom in the food industry. In line with that, the objective of our business is to achieve the stated vision and mission. Under this Business Plan, we will cover the Administrative Plan, Marketing Plan, Operational Plan as well as Financial Plan. All these will help to ensure the effectiveness of our Business Plan. Plus, it will guide us along the running of our business so that we are able to perform well. As a conclusion, this business focus more on our farming technique and what makes our business is different from the other mushroom company. As a new comer to this business, we ought to be competitive and productive.